19.7k views
3 votes
Find an explicit rule for the nth term of the sequence.

7, -7, 7, -7, ... (5 points)
Select one:
a. an = 7 • (-1)n-1
b. an = 7 • (-1)n
c. an = 7 • 1n-1
d. an = 7 • 1n+1

User ITHelpGuy
by
5.8k points

2 Answers

4 votes

Answer:

an=7•(-1)^n-1

Explanation:

User Bthota
by
5.3k points
2 votes

Answer:

(a) The ONLY explicit rule for the nth term of the sequence is
a_n = 7  * (-1)^(n-1)\\.

Explanation:

Here, the given sequence is 7, -7, 7, -7, ...

The first term = 7, Second term = -7, Third term =-7 and so on..

Now check the given sequence for each given formula, we get:

(1)
a_n = 7  * (-1)^(n-1)\\

Now, for n = 1 :
a_1 = 7  * (-1)^(1-1)\\


= 7 * (-1)^0 =  7 * 1 = 7 \implies a_1 = 7

Similarly, for, n = 2:
a_2 = 7  * (-1)^(2-1)\\


= 7 * (-1)^1 =  7 * (-1) = -7 \implies a_2 = -7

Hence, the given formula satisfies the given sequence.

(2)
a_n = 7  * (-1)^(n)\\

Now, for n = 1 :
a_1 = 7  * (-1)^(1)\\


= 7 * (-1)^1 =  7 * (-1) = -7 \implies a_1 = -7

But, First term = 7

Hence, the given formula DO NOT satisfy the given sequence.

(3)
a_n = 7  * (1)^(n-1)\\

Now, for n = 1 :
a_1 = 7  * (1)^(1-1)\\


= 7 * (1)^0 =  7 * 1 = 7 \implies a_1 = 7

Similarly, for, n = 2:
a_2 = 7  * (1)^(2-1)\\


= 7 * (1)^1 =  7 * (1) = 7 \implies a_2 = 7

But, Second term = -7

Hence, the given formula DO NOT satisfy the given sequence.

(4)
a_n = 7  * (1)^(n+1)\\

Now, for n = 1 :
a_1 = 7  * (1)^(1+1)\\


= 7 * (1)^2 =  7 * 1 = 7 \implies a_1 = 7

Similarly, for, n = 2:
a_2 = 7  * (1)^(2+1)\\


= 7 * (1)^3 =  7 * (1) = 7 \implies a_2 = 7

But, Second term = -7

Hence, the given formula DO NOT satisfy the given sequence.

So, the ONLY explicit rule for the nth term of the sequence is
a_n = 7  * (-1)^(n-1)\\.

User PmbAustin
by
5.2k points